2019
DOI: 10.7759/cureus.6030
|View full text |Cite
|
Sign up to set email alerts
|

Our Experience with Transcatheter Aortic Valve Replacement Medication Outcomes from 2013 to 2016

Abstract: BackgroundAortic stenosis is classified as stenosis that can be caused by a congenital disability in infants and children but is more commonly produced by a degenerative process of calcification and scarring of the valve in the later decades of life. High systemic pressure and hemodynamic disturbances characteristic of this area of the cardiovascular system makes the aortic valve susceptible to plaque and cholesterol buildup over time, similarly to atherosclerosis, contributing to the pathology of aortic steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The result of analysis for twelve studies 9-11,15-19,21,23,25,26 that reported HR, also favored statin therapy (HR = .78, 95% CI 0.64-.93, P = .0063; I 2 = 53.2%, Q value = 23.51, P = .0149) (Figure 4).
Figure 4.Comparison of the impact of statin vs no statin therapy on all-cause mortality in studies that reported hazard ratio.
…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The result of analysis for twelve studies 9-11,15-19,21,23,25,26 that reported HR, also favored statin therapy (HR = .78, 95% CI 0.64-.93, P = .0063; I 2 = 53.2%, Q value = 23.51, P = .0149) (Figure 4).
Figure 4.Comparison of the impact of statin vs no statin therapy on all-cause mortality in studies that reported hazard ratio.
…”
Section: Resultsmentioning
confidence: 95%
“…The sensitivity analysis of the 9 high-quality studies 9-11,16,17,21-23,28,29 with low risk of bias indicated a lower risk of all-cause mortality in patients who received statin therapy (HR = .75, 95% CI 0.66-.85, P < .0001; I 2 = 55.3%, Q value = 17.90, P = .0220) (Figure 3). However, the analysis for low-quality studies did not show any beneficial effect for statin therapy (HR = .92, 95% CI 0.70–1.20, P = .52; I 2 = 29.0%, Q value = 9.86, P = .1969).
Figure 3.Comparison of the impact of statin vs no statin therapy on all-cause mortality among high-quality and low-quality studies.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations